Genomic heterogeneity in synchronous hepatocellular carcinomas. Issue 5 (1st November 1999) - Sirivatanauksorn, Y; Sirivatanauksorn, V; Bhattacharya, S; Davidson, B R; Dhillon, A P; Kakkar, A K; Williamson, R C N; Lemoine, N R
Abstract : BACKGROUND: Hepatocellular carcinoma (HCC) arising in cirrhosis is frequently multifocal. Whether HCC develops monoclonally or multiclonally is an unresolved question. Of the multiple tumour nodules present in many patients, it has not been established whether the smaller lesions represent intrahepatic metastases or de novo cancers. AIMS: To assess the degree of genomic heterogeneity in synchronous HCCs in cirrhosis. METHODS: The arbitrarily primed polymerase chain reaction technique was utilised to compare the DNA fingerprint of HCCs and regenerative nodules (RNs) removed from cirrhotic explant livers. RESULTS: Polymorphic genomic heterogeneity was noted in 54 HCCs and 31 RNs microdissected. Even satellite nodules in close proximity within the same segment of the liver were found to have distinct genomic patterns. CONCLUSION: Such genomic heterogeneity in synchronous HCCs may explain poor patient survival after surgical resection. If the smaller tumours are de novo lesions rather than metastases (as these data suggest), then current concepts regarding liver resection as a curative treatment modality for HCC may require reassessment.